Tendências temporais do câncer de mama: análise a partir dos registros hospitalares de câncer no Brasil - Martins, Milena Colares Tupinambá (2025)
Breast cancer has a multifactorial etiology, involving hormonal, reproductive, genetic and lifestyle factors. For the three-year period 2023-2025, it is the most common type of cancer (except non-melanoma skin cancer), with 74,000 cases. Law No. 12.732/2012 sets a deadline of 60 days for patients with neoplasms to start treatment and 30 days for the necessary diagnostic tests to be carried out. However, delays in access to screening tests, biopsies and the start of treatment are still a recurring problem in Brazil. Faced with the challenges posed by cancer and the need for hospital surveillance, it has become essential to set up the Hospital Cancer Registry (RHC), which is responsible for collecting data on cancer cases, primarily with a view to improving the care and treatment of these patients. The aim of this study was to find out about the sociodemographic and care characteristics of malignant breast tumors in women, and the associations between clinical stages. This is a ecological, retrospective, secondary-based study. Data collected from information in the Integrator Module of Hospital Cancer Registries. Collected from 2015 to 2021. The data was downloaded in November 2024 and is publicly accessible. Included were women in all age groups (divided into categories), who received a diagnosis with code C50. The total number of records was 214,074. The statistical analysis was based on a description of the data, including variables such as: age group, schooling, marital status, race and Federative Unit of the hospital unit and TNM staging. Another analysis concerned the time interval between the first consultation, the date of diagnosis and the start of treatment. A simple correspondence analysis was then carried out to assess the association between clinical stage and the variables. The majority of women in all stages had incomplete primary education (26.9%). Stage 3 was correlated with being single and in a consensual union, while stage 2 was correlated with being separated, married and widowed. All stages of breast cancer are concentrated in women aged between 30 and 59 (59.8%). Black women account for the majority in the more advanced stages (36.46%), while in stage 1 the majority are white women (34%). The Southeast region concentrates cases in all stages (48.4% of records in stage 4), followed by the Northeast region, which comes second in all stages, with the exception of stage 1 (South region 22.6%). Most patients were diagnosed within the time limit recommended by law, but treatment exceeded the 60-day limit. What stands out is the high frequency of patients with advanced cancer stages and the delay in diagnosis, but especially in starting treatment. Advanced stages were associated with incomplete primary education, age between 30 and 59, and black race. In this context, it is necessary to prioritize measures capable of guaranteeing early detection and timely treatment for breast cancer patients, as well as improving information systems so that these actions can be monitored.